Tìm X : X x 2013 – x = 2013 x 2011 + 2013

Question

Tìm X :
X x 2013 – x = 2013 x 2011 + 2013

in progress 0
Savannah 2 tháng 2021-08-06T22:13:10+00:00 2 Answers 5 views 0

Answers ( )

    0
    2021-08-06T22:14:25+00:00

     Ta có : $x×2013-x = 2013×2011+2013$

    $\to x×(2013-1) = 2013×(2011+1)$

    $\to x×2012 = 2013×2012$

    $\to x=2013$

    0
    2021-08-06T22:14:30+00:00

    X x 2013 – X = 2013 x 2011 + 2013

    X x (2013 – 1) = 2013 x (2011 + 1)

    X x 2012 = 2013 x 2012

    ⇒ X = 2013

Leave an answer

Browse

35:5x4+1-9:3 = ? ( )